Understanding The role of digitalisation in funeral insurance claims in South Africa - Suliman, Mohamed Ameen (University of the Witwatersrand, Johannesburg, 2024)
This research report studies the role of digitalisation in funeral insurance claims in South Africa. The study seeks to understand the benefits as well as the challenges faced by digitalisation in funeral insurance claims in South Africa. A qualitative research study was undertaken within a large funeral insurer based in South Africa. Semi-structured interviews were conducted with employees of the organisation who had expert knowledge of funeral insurance claims. Inductive thematic analysis was the method of choice for understanding the results. The study's findings were that digitalisation has a role to play across multiple points in the claims journey. Benefits of digitalisation include driving efficiency of back-end processes with applications like automation of the claims process as well as supporting fraud detection with artificial intelligence. Challenges of digitalisation include the adoption of digital tools by the insurer and the customer, cybersecurity and the socio-economic dynamics of customers in rural areas. Insurers would benefit from digitalising their workflows to unlock efficiencies within their existing claims processes. Customers would benefit from these efficiencies, as well as the enhanced customer experience that digital channels can provide. The study was limited to employees within a single funeral insurer in South Africa. Further study could be to replicate the study across the broader funeral insurance industry, capturing more players within the market. Additionally, further study on the interactions between particular technologies and their effect on the claims process would be valuable
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Funeral Insurance; Claims; Digitalisation; Digital Divide; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth